2009
DOI: 10.1007/bf03195677
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of 19 porcine SNPs on growth rate, meat content and selection index

Abstract: A total of 306 boars (108 Large White and 198 Landrace) were genotyped for 52 candidate SNPs to determine which of the polymorphisms influence growth rate, meat content and selection index. The effects of SNPs were estimated by a mixed linear model including a random additive polygenic animal effect, fixed effects of SNPs including additive, and pairwise additive-by-additive epistases, year*season of birth, breed and RYR1 genotype. In order to estimate all possible pairwise SNP combinations without overparamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…On the other hand, an interaction among and within loci may also be shown in the ranking of chromosomes. Complex genetic determination of meatness has been reported by a number of authors (Kamiński et al, 2009;Srikanchai et al, 2010;Weisz et al, 2011;Fontanesi et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, an interaction among and within loci may also be shown in the ranking of chromosomes. Complex genetic determination of meatness has been reported by a number of authors (Kamiński et al, 2009;Srikanchai et al, 2010;Weisz et al, 2011;Fontanesi et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
“…Skinner et al (2006) suggested potential associations of the gene with swine skatole levels, however this trait is not directly connected with meatness. This locus has already been recommended as potentially associated with pork traits by Kamiński et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…No previous studies have described an association between alteration in MyF6 (also known as MRF4) and phenotypic traits in sheep. However, variants in this gene were associated with growth 50,51 and carcass 52,53 traits in pigs. In cattle, effects on growth 54 and carcass 55 traits were also reported.…”
Section: Association Analysismentioning
confidence: 98%